NILAI KARAKTER DAN HASIL PEMBELAJARAN SOSIOLOGI - Fatmah Fatmah; Pargito Pargito; Trisnaningsih Trisnaningsih (Faculty of Teacher Training and Education, University of Lampung, 2014)
This reserach aims to implement learning model which can improve the character values of the student as nurturant effect in teaching and learning process by comparing problems based learning in group or individually in learning sociology. The researcher used quasi experimental research method in conducting this research. Observation sheet and test are used as the instruments. In analysing the data, the researcher used tabulation to see the improvement of character values and T-test to know the difference of student learning result. The result of this research shows that the students is better in developing their character building when they solved problems in group than solving them individually. Along with that result, the average score of the student learning result also shows better when the learning process with problems based learning in group compared to the learning result which the process of problems based learning in individually.Tujuan penelitian untuk menerapkan model pembelajaran yang dapat mengembangkan nilai karakter yang merupakan dampak pengiring pembelajaran, dengan membandingkan pembelajaran berbasis masalah secara kelompok dan individu dalam pembelajaran sosiologi. Metode penelitian yang digunakan adalah metode eksperimen quaisy. Instrumen penelitian berupa lembar observasi dan tes, analisis data menggunakan diskriptif kualitatif untuk perubahan nilai karakter dan t-tes untuk mengetahui perbedaan hasil belajar. Hasil penelitian menunjukkan bahwa nilai karakter pembelajaran berbasis masalah secara kelompok lebih baik dibandingkan pembelajaran berbasis masalah secara individu. Demikian pula rerata hasil belajar yang menggunakan pembelajaran berbasis masalah secara kelompok lebih tinggi dibandingkan menggunakan model pembelajaran berbasis masalah secara individu.Kata kunci: hasil belajar, nilai karakter, pembelajaran kelompok